Meningoencephalitis caused by thermal disbudding in goat kids - XYLOURI (Ε. ΞΥΛΟΥΡΗ), E.; SABATAKOU (Ο. ΣΑΜΠΑΤΑΚΟΥ), O.; SAKELLARIADI (SAKELLARIADI Th.), Th. (Journal of the Hellenic Veterinary Medical Society, 2018)
A case of kids' meningoencephalitis due to head heat application during a thermal disbudding procedure is described. The case was observed in an organic goat farming where the kids about the 7-8th day after their birth were exposed to the application of excessive heat (with an electric device) during disbudding. 2,2% of the kids presented neurological signs and died in few days. The post mortem examination confirmed that the cause was destruction of the frontal bone, at the point where the thermal electric procedure was applied, leading to irreparable injury.